PERAN ZAKAT, INFAQ DAN SEDEKAH DALAM PEMBERDAYAAN MASYARAKAT MISKIN DI KABUPATEN TANGERANG (Studi Kasus Program Hibah Rumah Siap Huni Kopsyah BMI) - Dhany Hermawan; Atep Hendang Waluya (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
The purpose of this study was found out how the role of ZIS (Zakat, Infaq and Sadaqah) in the empowerment of poor people through the habitable home grant (hibah) program in Tangerang regency. The kind of this research was a field research that used a research survey method, and the instrument used was an  unstructured interview. The primary of the data sources were obtained by the interviews to the Zakat, Infaq and Sadaqah team of Kopsyah BMI. The secondary data were obtained from library studies. The technique of analysis data were carried out by steps as follows : the collection of the data, reduction of the data, presentation of the data, and the last steps of the technique was conclusion.  ZIS were managed by the Kopsyah BMI which was the Baznas zakat collection unit in Tangerang regency had the roles in empowering the poor. Within 2 years, from 2017 and 2018 the Kopsyah BMI had build 21 houses in Tangerang regency that meets the criteria of habitable home. In addition, since 2015 to 2018 the Kopsyah BMI   had carry out of empowering the poor by building 72 houses that qualified of the habitable homes’ rules of their mutual benevolent funds.